2014
DOI: 10.1002/acp.3062
|View full text |Cite
|
Sign up to set email alerts
|

‘This Is the Person You Selected’: Eyewitnesses' Blindness for Their Own Facial Recognition Decisions

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(66 citation statements)
references
References 52 publications
(80 reference statements)
21
43
1
Order By: Relevance
“…Experiment 1 demonstrated that the misinformation effect could be elicited from participants by telling them they had reported remembering episodic details in a different way from how they had earlier reported remembering those details. Experiment 2 generalized these findings to another memory task, eyewitness identification, and demonstrated that blindness to the manipulation, rather than mere exposure to the manipulation, drives subsequent memory change, consistent with previous theoretical and experimental work (Johansson et al, 2014;Sagana et al, 2014;Tousignant et al, 1986). We call this novel consequence of choice blindness on eyewitness memory memory blindness: When witnesses are exposed to manipulated versions of their own memory reports, they often fail to notice the manipulation, and their memories often change to be consistent with those altered reports.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Experiment 1 demonstrated that the misinformation effect could be elicited from participants by telling them they had reported remembering episodic details in a different way from how they had earlier reported remembering those details. Experiment 2 generalized these findings to another memory task, eyewitness identification, and demonstrated that blindness to the manipulation, rather than mere exposure to the manipulation, drives subsequent memory change, consistent with previous theoretical and experimental work (Johansson et al, 2014;Sagana et al, 2014;Tousignant et al, 1986). We call this novel consequence of choice blindness on eyewitness memory memory blindness: When witnesses are exposed to manipulated versions of their own memory reports, they often fail to notice the manipulation, and their memories often change to be consistent with those altered reports.…”
Section: Discussionsupporting
confidence: 78%
“…This rate of change to the target face is significantly greater than we would expect by chance, χ 2 (1, N = 94) = 13.58, p < .001. (Sagana et al, 2014). When participants detected the misinformation, their responses were similar to those when the misinformation was not presented at all.…”
Section: Target Fillermentioning
confidence: 73%
See 3 more Smart Citations